Differences in susceptibility to photoinhibition do not determine growth rate under moderate light in batch or turbidostat-a study with five green algae - Mattila Heta; Valev Dimitar; Mishra Kumud B.; Havurinne Vesa; Virtanen Olli; Antinluoma Mikko; Tyystjärvi Esa (ACAD SCIENCES CZECH REPUBLIC, INST EXPERIMENTAL BOTANY, 2022)
To understand growth limitations of photosynthetic microorganisms, and to investigate whether batch growth or certain photosynthesis-related parameters predict a turbidostat (continuous growth at constant biomass concentration) growth rate, five green algal species were grown in a photobioreactor in batch and turbidostat conditions and their susceptibilities to photoinhibition of photosystem II as well as several photosynthetic parameters were measured. Growth rates during batch and turbidostat modes varied independently of each other; thus, a growth rate measured in a batch cannot be used to determine the continuous growth rate. Greatly different photoinhibition susceptibilities in tested algae suggest that different amounts of energy were invested in repair. However, photoinhibition tolerance did not necessarily lead to a fast growth rate at a moderate light intensity. Nevertheless, we report an inverse relationship between photoinhibition tolerance and minimum saturating irradiance, suggesting that fast electron transfer capacity of PSII comes with the price of reduced photoinhibition tolerance.